Increased inactivation of Saccharomyces cerevisiae by protraction of UV irradiation. - Sommer, R (1996)
The principle of equi-effectivity of the product of intensity and exposure time (principle of Bunsen-Roscoe) of UV irradiation has been assumed to be valid for the inactivation of microorganisms in general. Earlier studies claimed higher survival of Escherichia coli B/r with fractionated irradiation compared with single-exposure survival. However, data on the inactivation effect of protraction of UV irradiation are not available. By means of a specially designed UV irradiation apparatus which secured absolute UV dose measurements throughout the experiments, the effects of variation of UV irradiation intensities (253.7 nm) and exposure times were tested on the inactivation of a bacterial virus (Staphylococcus aureus phage A994), a vegetative bacterial strain (E. coli ATCC 25922), and bacterial spores (Bacillus subtilis ATCC 6633) as well as three haploid laboratory strains (RC43a, YNN281, and YNN282) and two diploid strains (commercial bakery yeast strain and laboratory strain YNN281 x YNN282) or yeast (Saccharomyces cerevisiae) and spores of the latter diploid yeast strain. Each test organism was exposed to three UV intensities (0.02, 0.2, and 2 W/m2), with corresponding exposure times resulting in three dose levels for each intensity. Differences in inactivation rates were tested by analyses of variance and Newman-Keuls tests. Virus and bacteria showed no differences in inactivation rates by variation of intensities and exposure times within selected UV doses; hence, the principle of Bunsen-Roscoe could not be rejected for these strains. However, in the eukaryotic test strains of S. cerevisiae longer exposure times with lower intensities led to enhanced inactivation in both haploid and diploid strains, with a more pronounced effect in the diploid yeast strains, whereas in yeast spores in this dose rate effect could not be observed.